Enrichment of core competencies to maximize health system impact: An analysis of an embedded research training program - Bahar Kasaai; Erin Thompson; Richard H Glazier; Meghan McMahon (Wiley, 2024)
Abstract Introduction The Health System Impact (HSI) Fellowship is an embedded research training program that aims to prepare doctoral trainees and postdoctoral fellows for stronger career readiness and greater impact as emerging leaders within and beyond the academy, including in learning health systems (LHS). The program supports fellows to develop 10 leadership and research competencies that comprise the Enriched Core Competency Framework in Health Services and Policy Research through a combination of experiential learning, mentorship, and professional development training. This study tracks competency development of HSI fellows over time and examines fellows' perspectives on which program design elements support their competency development. Methods A competency assessment tool developed for the program was independently completed by 95 postdoctoral and 36 doctoral fellows (self‐assessments) and their respective 203 dyad (academic and health system) supervisors in the 2017 to 2019 program cohorts, who independently rated the strength of fellows' 10 competencies at baseline and several points thereafter. Competency strength ratings were analyzed to understand change over time and differences in ratings across groups (between fellows' sex, supervisor type, and supervisor vs. fellow). Program design element ratings were examined to understand perspectives on their contribution toward fellows' competency development. Results Fellows' competency strength significantly improved in all 10 domains over time, based on independent assessments by the fellows and their dyad supervisors. Supervisors tended to rate the fellows' competency strength higher than the fellows did. Differences in competency ratings between male and female fellows (self‐assessments) and between academic and health system supervisors were either negligble or not significant. Fellows identified all nine program design elements as enriching their competency development. Conclusion The HSI Fellowship provides an opportunity for fellows to develop the full suite of enriched core competencies and to prepare a cadre of emerging leaders with the skills and experience to contribute to the advancement of LHS.